Analisis Pembelajaran Menulis Puisi Dengan Menggunakan Media Audiovisual - Kemit, Esterina Meriahta Br; Putrayasa, Ida Bagus; Nurjaya, I Gede (Jurnal Penelitian Mahasiswa Indonesia, 2024)
The aims of this study were (1) to describe the process of implementing learning to write poetry using audiovisual media in class VIII students of SMP Negeri 4 Anggrek Singaraja, (2) to describe the results of learning to write poetry using audiovisual media in class VIII students of SMP Negeri 4 Singaraja. Anggrek SMP Negeri 4 Singaraja, (3) explained the obstacles that occur in learning to write poetry using audiovisual media in class VIII Anggrek SMP Negeri 4 Singaraja. The research design is descriptive research and the data collection methods are observation, documentation, and interviews with data collection instruments as guidelines for observation sheets, cameras, and recording devices. The results of the study show that (1) in the implementation of learning to write poetry using audiovisual media, there are three activities carried out, namely the opening, core and closing activities in the implementation of learning to write poetry. (2) Student learning outcomes in learning to write poetry using audiovisual media provide an overview of the extent to which students' ability to write poetry using audiovisual media can be seen from the results of student work examined by the teacher sorted according to students. 'ability. from the acquisition of the largest value to the smallest value. (3) Obstacles in learning to write poetry using audiovisual media, namely showing several obstacles faced by Indonesian language teachers in carrying out learning to write poetry using audiovisual media, namely time management which is still ineffective, students' different abilities in writing poetry, students' focus on learning writing poetry is still lacking.